Impact of infill development on prices of existing apartments in Finnish urban neighbourhoods - Ahvenniemi, Hannele; Pennanen, Kyösti; Knuuti, Antti; Arvola, Anne; Viitanen, Kauko (International Journal of Strategic Property Management, 2018)
Popularity of infill development is increasing because of the environmental benefits and cost saving potential it provides, which relate to the possibility to use existing infrastructure and services. However, the impact of infill development on value of existing properties has not been studied to a sufficient extent. Therefore, the aim of our study is to analyse whether infill development affects the prices of existing apartments. We carried out statistical analysis based on data from seven case neighbourhoods, and prices of more than 6000 housing transactions from one decade. The results of our analysis do not support the hypothesis of infill development affecting positively existing housing prices, but neither did the study show a significant negative effect. Both amenity effect and negative externalities may provide explanations as to why property values do not change due to infill development.